Desulfurisasi Batubara Menggunakan Larutan Ekstrak Belimbing Wuluh (Everrhoa Bilimbi L) - Amin, Muhammad; Birawidha, David Candra; Isnugroho, Kusno; Hendronursito, Yusuf; Muttaqqi, Muhammad Al; Prilitasari, Nurbaiti Marsas (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2019)
Desulphurization process can improve the quality of coal and reduce the environmental pollution. In this study, the method used for desulphurization process was a leaching method using wuluh starfruit extract as a leaching agent. Starfruit extract obtained by grinded, filtered and extracted the starfruit solution. Coal was crushed by using a grinding ball mill, sifted to obtain samples of 80 mesh, 120 mesh, and 150 mesh. Coal was added with starfruit extract, heated on a hotplate stirrer at a temperature of 110oC, 300 rpm of stirring speed and 3, 4 , 5 hours of leaching time. Leachate solution were analyzed using XRF test. The results of the study showed that 80, 120 and 150 mesh could produce 1.777%, 1.556% and 1.053% of sulfur, respectively. Maximum decrease of sulfur occurred in 150 mesh with 5 hours of leaching time which could reach 0.261% of concentration. Ash content also could decreased from 11.43% to 6.18% and fixed carbon content from 42.15% rose to 51.33%. The desulphurization process using starfruit extract was influenced by the grain size of the coal and the contact time of leaching. The finer the grain size of the coal and the longer the leach contact time, the smaller the sulfur content obtained in the coal after the desulfurization process was carried out